THE EFFECTIVENESS OF INFORMATION SERVICES USING A FEMINIST THERAPY APPROACH TO IMPROVE STUDENTS' UNDERSTANDING OF GENDER ROLES AT MAN 1 TAKENGON - Nazwa Elyana; Alfin Siregar (Conciencia, 2023)
This study aims to determine the effectiveness of information services using a feminist therapy approach to improve students' understanding of gender roles at MAN 1 Takengon. This research uses quantitative research quasi experiment. The population of this research consisted of 208 students and the research sample consisted of 70 students determined by cluster random sampling technique. Data collection instruments used observation and questionnaires. Data analysis techniques used normality test, homogeneity test and hypothesis testing in the form of paired sample T-Test test. The results of this study indicate that there is a significant difference between the pre-test and post-test scores, with a significance value (2-tailed) P = 0.000 < 0.05. This means that information services are effective for increasing students' understanding of gender roles.